Caractérisation du phénomène de brunissement du vitrail et évaluation de traitements de réduction - Elisabeth Venault de Bourleuf (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Manganese (Mn), minor element being part of the chemical composition of medieval glass, appears to be highly involved in the deterioration process leading to the appearance of brown stains. As a consequence, stained-glass windows lose their transparency, the artefacts ending up illegible. This master thesis was focused on visual and chemical characterization of the pathology. Then, a review of the existing treatments was attempted and six selected products were tested in order to validate different protocols tried in previous studies.